Teachers’ Policy in Designing English Syllabus at Grade XI - ADAM, ADAM (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
The present study aims to analyze the Teachers’ Policy in designing English teaching syllabus at grade XI of SMAN 2 Batam. In addition to analyzing the way the teachers design their syllabus, the researcher also analyzed the problems faced by the teachers in designing the English teaching syllabus. The participants of this study were 3 English teachers who were teaching class XI of SMAN 2 Batam. The data were obtained from the interview and observation. The Supporting instruments used in this research were tape recorder, and camera. The data were analyzed through, data managing, reading and memoing, describing, classifying, and interpreting. Based on the findings, the three English teachers had followed the steps of syllabus design suggested in BSNP (Badan Standar Nasional Pendidikan or The Council of National Education Standard 2006) with respect to adapting each component of the syllabus with the teaching and learning context. It can also be concluded from the findings that the three English teachers still needed to get themselves familiar with some of the kinds of evaluation necessary for assessing a learning process. On the other hand, Most of the problems faced by the teachers in designing the English teaching syllabus were first not being able to accomplish the relationship between each components of the syllabus with the first component namely the standard competency and basic competency. The second problem was the three English teachers did not have sufficient knowledge on how to sequence the order of the difficulty level of the lesson as well as finding appropriate materials that suit their students’ need. The third problem they had was they were not familiar with some types of evaluation which are very helpful in assessing a learning process. And the last problem they faced was managing time allocation. A lot of the time they were not able to finish and complete a lesson within one period of a school term due to the lack of time.Keywords: teachers’ policy and English teaching syllabus